2002
DOI: 10.1103/physrevb.66.075216
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of interstitialH2in crystalline silicon

Abstract: The dynamics of interstitial H 2 and its isotopes in crystalline silicon have been studied by using a potentialenergy function for the molecule that consists of the superposition of potentials for two separated hydrogen atoms as generated from the quantum-mechanical calculations of Porter, Towler, and Needs. The rotational properties were calculated using the approach of Martin and Fowler and the vibrational properties of the molecules as a whole were obtained. The results of these calculations indicate nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
3
17
1
Order By: Relevance
“…Much better agreement with the experimental ortho-para splitting has been found by a similar method but using a quite different perturbing potential. 21 In conclusion, we have found that the IR activity of the molecule does not require a movement of the molecule away from the tetrahedral site, as has been thought previously, but a polarization of the surrounding lattice. The effective charges relating to the strengths of the IR transition are then the same for H 2 as D 2 and in agreement with the data, unlike a model where the activity arises from a displacement of the molecule from the lattice site.…”
Section: Rapid Communicationssupporting
confidence: 78%
See 1 more Smart Citation
“…Much better agreement with the experimental ortho-para splitting has been found by a similar method but using a quite different perturbing potential. 21 In conclusion, we have found that the IR activity of the molecule does not require a movement of the molecule away from the tetrahedral site, as has been thought previously, but a polarization of the surrounding lattice. The effective charges relating to the strengths of the IR transition are then the same for H 2 as D 2 and in agreement with the data, unlike a model where the activity arises from a displacement of the molecule from the lattice site.…”
Section: Rapid Communicationssupporting
confidence: 78%
“…The effective charges relating to the strengths of the IR transition are then the same for H 2 as D 2 and in agreement with the data, unlike a model where the activity arises from a displacement of the molecule from the lattice site. 21 The splitting of the lines observed under stress, or by the presence of a neighboring oxygen impurity, can be modeled in a simple way and the results are in reasonable agreement with experiment. The analysis shows that there are other as yet undetected IR transitions at low temperatures albeit with low intensities.…”
Section: Rapid Communicationsmentioning
confidence: 55%
“…Furthermore, molecular dynamics calculations indicate that the H 2 ; HD and D 2 molecules in Si behave as nearly free rotators, bouncing within the interstitial region [13]. This conclusion is supported by our own model calculations [15] which suggest a rotational barrier of only B0:01 eV; more than an order of magnitude smaller than argued [12] would be needed for consistency with a static model.…”
Section: Introductionsupporting
confidence: 54%
“…We have noted that a dipole moment may be induced on the H 2 molecule by virtue of its zeropoint motion, which dynamically breaks the exact equivalence of the two atoms [15,17]. Recently, Hourahine and Jones have pointed out that a dipole moment on the neighboring Si atoms is induced by the quadrupole moment of the rotating H 2 molecule, even when the molecule is on center [22].…”
Section: Article In Pressmentioning
confidence: 96%
“…The frequency range for the Mo-H modes is 1800-2000 cm À1 . In addition, adsorbed undissociated molecular species H 2 , H dþ 2 and H dÀ 2 should be considered, as they have been argued to exist on metals based on conductivity and work function measurements [13,34], and recently proven to exist in silicon [35]. Reasons for the lack of detection of hydrogen species on MoS 2 solids may be the high absorbance of this material in the region of S-H and Mo-H stretching modes as well as low concentrations, low oscillator strengths particularly for weakly adsorbed H 2 , and homogeneous or inhomogeneous line broadening.…”
Section: Introductionmentioning
confidence: 99%